2014
DOI: 10.1016/b978-0-12-801284-0.00002-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Pathways in Alcohol Consumption: Evidence from Behavioral and Genetic Studies in Rodents and Humans

Abstract: Immune or brain proinflammatory signaling has been linked to some of the behavioral effects of alcohol. Immune signaling appears to regulate voluntary ethanol intake in rodent models, and ethanol intake activates the immune system in multiple models. This bidirectional link raises the possibility that consumption increases immune signaling, which in turn further increases consumption in a feed-forward cycle. Data from animal and human studies provide overlapping support for the involvement of immune-related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 126 publications
(169 reference statements)
6
69
0
1
Order By: Relevance
“…Preclinical as well as clinical studies have shown the potent role of inflammation for the development of alcohol-dependence, as nicely described in a recent review article. 38 Furthermore, in the study commented here, as well as in previous studies from our group. 32 proinflammatory markers were related to the gut permeability, and in the same population these markers were shown to correlate positively with craving at the beginning of withdrawal while the antiinflammatory cytokine IL-10 correlated negatively with depression, anxiety and craving at the end of withdrawal.…”
Section: Which Pathways Of the Gut-brainmentioning
confidence: 55%
“…Preclinical as well as clinical studies have shown the potent role of inflammation for the development of alcohol-dependence, as nicely described in a recent review article. 38 Furthermore, in the study commented here, as well as in previous studies from our group. 32 proinflammatory markers were related to the gut permeability, and in the same population these markers were shown to correlate positively with craving at the beginning of withdrawal while the antiinflammatory cytokine IL-10 correlated negatively with depression, anxiety and craving at the end of withdrawal.…”
Section: Which Pathways Of the Gut-brainmentioning
confidence: 55%
“…However, synaptosomal fractions contain glial plasma membranes, and p75NTR is moderately expressed in glia cells including astrocytes (Cragnolini and Friedman, 2008). Astrocytic signaling has been shown to contribute to adverse phenotypes associated with alcohol exposure (Lee et al, 2013;Bull et al, 2014;Robinson et al, 2014). Since the fractionation method used herein cannot differentiate between possible changes in p75NTR localization in neurons versus glia, we cannot exclude the possibility that p75NTR in nonneuronal cells such as astrocytes contributes to the maintenance of excessive alcohol drinking.…”
Section: Discussionmentioning
confidence: 81%
“…Research in adult animals and humans has shown that neuroimmune signaling can influence ethanol intake and ethanol actions, with ethanol exposure conversely inducing proinflammatory signaling in brain (Robinson et al, 2014). Hence, it is not surprising that alcohol exposure during adolescence induces lasting increases in expression of neuroimmune genes, including a variety of proinflammatory signaling molecules, along with activation of the innate immune system receptor, Toll-like receptor 4 (TLR4) (see Crews & Vetreno, 2014, for review).…”
Section: Alcoholmentioning
confidence: 99%